Legal Protection For The Community Against Wastewater Pollution Of The Production Of Woven Ikat Sarongs Based On Law Number 32 Of 2009 - Faradina Nur Hidayatun Nissa; Soediro Soediro; Astika Nurul Hidayah (Faculty of Law Universitas Muhammadiyah Purwokerto, 2021)
Abstract Regional economic development aims to manage existing resources and to create new jobs and help the regional economy. One way to do this is by opening industrial activities that encourage people to have the skills to produce something that can generate profits, such as the production of woven ikat sarongs. This has a positive impact, namely helping the village economy, but there is also a negative impact, namely environmental pollution. This study aims to find out how the legal protection provided by the government to the community is related to environmental pollution in areas that produce ikat sarongs, and what are the obstacles in providing legal protection. The method used in this research is normative juridical, where the law is conceptualized as what is written in the legislation. Sources of data in this study using secondary data and primary data in assisting the research process. The data collection method in this study uses a literature study, namely by collecting literature such as books, scientific journals, and primary legal materials to support research as well as identification and clarification of legal facts by asking questions to sources according to research needs. Based on the results of research and discussion, people in areas that produce ikat sarongs get a form of protection in the form of the law of making communal Wastewater Treatment (WWTP), but until now they have not received legal protection caused by several inhibiting factors, namely there is no budget for making communal WWTP and lack of vacant land. around North Wanarejan VillageKeywords: Legal Protection, Industry, Pollutionn